Lnc-AIFM2-1 promotes HBV immune escape by acting as a ceRNA for miR-330-3p to regulate CD244 expression - Xie, Chengxia; Wang, Shengjie; Zhang, He; Zhu, Yalan; Jiang, Pengjun; Shi, Shiya; Si, Yanjun; Chen, Jie (Frontiers in Immunology, 2023)
Chronic hepatitis B (CHB) virus infection is a major risk factor for cirrhosis and hepatocellular carcinoma (HCC). Hepatitis B virus (HBV) immune escape is regulated by the exhaustion of virus-specific CD8+ T cells, which is associated with abnormal expression of negative regulatory molecule CD244. However, the underlying mechanisms are unclear. To investigates the important roles of non-coding RNAs play in CD244 regulating HBV immune escape, we performed microarray analysis to determine the differential expression profiles of long non-coding RNAs (lncRNAs), microRNAs (miRNAs), and mRNAs in patients with CHB and patients with spontaneous clearance of HBV. Competing endogenous RNA (ceRNA) was analyzed by bioinformatics methods and confirmed by the dual-luciferase reporter assay. Furthermore, gene silencing and overexpression experiments were used to further identify the roles of lncRNA and miRNA in HBV immune escape through CD244 regulation. The results showed that the expression of CD244 on the surface of CD8+ T cells was significantly increased in CHB patients and in the co-culture system of T cells and HBV-infected HepAD38 cells, which was accompanied by the reduction of miR-330-3p and the elevation of lnc-AIFM2-1. The down-regulated miR-330-3p induced the apoptosis of T cells by lifting the inhibition of CD244, which was reversed by miR-330-3p mimic or CD244-siRNA. Lnc-AIFM2-1 promotes the accumulation of CD244, which is mediated by decreased miR-330-3p, and then reduced the clearance ability of CD8+ T cells to HBV through regulated CD244 expression. And the injury in the ability of CD8+ T cells to clear HBV can be reversed by lnc-AIFM2-1-siRNA, miR-330-3p mimic, or CD244-siRNA. Collectively, our findings indicate that lnc-AIFM2-1 on CD244 by acting as a ceRNA of miR-330-3p contributes to HBV immune escape, which may provide novel insights into the roles of interaction networks among lncRNA, miRNA, and mRNA in HBV immune escape, highlighting potential applications of lnc-AIFM2-1 and CD244 for diagnosis and treatment in CHB.